Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
By adding F and Al to the lithium excess composite oxide and adding specific elements, the problem of durability and capacity reduction caused by transition metal dissolution is solved, and a lithium transition metal composite oxide with high capacity and high durability is achieved.
Patent Information
- Application Number
- CN202411614675.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-28
- Filing Date
- 2021-02-10
- Publication Date
- 2025-03-18
AI Technical Summary
In the case of lithium excess lithium transition metal composite oxide, the transition metal is easily dissolved, resulting in problems such as degradation of durability, rising resistance and reduced capacity.
Add F to the lithium-overcomplex oxide to inhibit the dissolution of the transition metal, and combine the addition of Al and more than two specific elements to optimize the composition of the lithium transition metal composite oxide to improve its stability and capacity.
Through this method, the high capacity and high durability of lithium transition metal composite oxide are achieved, and the performance of the battery is significantly improved.
Smart Images

Figure CN119650676A_ABST
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of February 10, 2021, an application number of 202180015436.6, and an invention name of “Positive electrode active material for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery”. Technical Field
[0002] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery using the positive electrode active material. Background Art
[0003] In non-aqueous electrolyte secondary batteries such as lithium-ion batteries, the positive electrode active material has a great influence on the battery performance such as input / output characteristics, capacity, and cycle characteristics. Among the positive electrode active materials, lithium transition metal composite oxides containing metal elements such as Ni, Co, Mn, and Al are generally used. The properties of lithium transition metal composite oxides vary greatly depending on their composition, so a lot of research has been conducted on the type and amount of added elements.
[0004] For example, Patent Document 1 discloses a positive electrode active material for a non-aqueous electrolyte secondary battery, which has a composition formula of Li x Ni 1-y Co y-z M z O 2-a X b (M is at least Al) indicates that the lattice constant of the a-axis measured by X-ray diffraction is The lattice constant of the c-axis is The ratio of the diffraction peak intensity of the (104) plane to the peak intensity of the (003) plane is 0.3 to 0.8.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 4197002 Summary of the invention
[0008] A lithium-excess composite oxide in which the molar ratio of Li to transition metal exceeds 1 has also been proposed. The lithium-excess composite oxide is expected to be a high-capacity next-generation positive electrode active material, but there are problems such as easy dissolution of transition metals. It is known that by adding F to the lithium-excess composite oxide, the dissolution of transition metals is suppressed and the durability is improved, but in this case, there are problems of increased resistance and reduced capacity.
[0009] The positive electrode active material for a nonaqueous electrolyte secondary battery as one embodiment of the present disclosure includes a composition formula Li x Mn y Ni z Ala M b O 2-c F c (wherein, M is two or more elements selected from Ti, Co, Si, Sr, Nb, W, Mo, P, Ca, Mg, Sb, Na, B, V, Cr, Fe, Cu, Zn, Ge, Zr, Ru, K, Bi; 1.0 < x ≤ 1.2, 0.4 ≤ y ≤ 0.8, 0 ≤ z ≤ 0.4, 0 < a < 0.01, 0 < b < 0.03, 0 < c < 0.1, x + y + z + a + b ≤ 2) the lithium transition metal composite oxide shown.
[0010] The non-aqueous electrolyte secondary battery as one aspect of the present disclosure includes: a positive electrode containing the above positive electrode active material; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and a non-aqueous electrolyte.
[0011] According to the present disclosure, a positive electrode active material with high capacity can be provided. The positive electrode active material according to the present disclosure can achieve both high capacity and high durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a cross-sectional view of a non-aqueous electrolyte secondary battery as an example of an embodiment. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0013] As described above, when F is added to the lithium-excess type composite oxide, the dissolution of the transition metal is suppressed and the durability is improved. On the contrary, the resistance increases and the capacity decreases. It should be noted that for the lithium transition metal composite oxide, if a large amount of Li is inserted and extracted, the crystal structure is likely to be destabilized, but by adding Al, the structure is stabilized. Therefore, by adding Al, charging can be performed up to a high voltage, which is beneficial to high capacity. However, high capacity as expected cannot be achieved only by adding Al.
[0014] The inventors of the present invention conducted in-depth research to solve the above problems and found that: in a lithium-excess type F-containing composite oxide containing at least Mn as a transition metal, high capacity is achieved by adding Al and two or more specific elements. When adding Al and two or more specific elements, for example, compared with the case of adding Al and one specific element, the capacity is specifically improved.
[0015] Hereinafter, with reference to the drawings, an example of an embodiment of the positive electrode active material for a non-aqueous electrolyte secondary battery and the non-aqueous electrolyte secondary battery using the positive electrode active material will be described in detail. It should be noted that it is initially contemplated to selectively combine a plurality of the following-described embodiments and modification examples.
[0016] In the following, a cylindrical battery is exemplified in which a wound electrode body 14 is accommodated in a bottomed cylindrical outer shell can 16, but the outer shell is not limited to a cylindrical outer shell can, and may be, for example, a square outer shell can (square battery), a coin-shaped outer shell can (coin-shaped battery), or an outer shell composed of a laminate sheet including a metal layer and a resin layer (laminated battery). In addition, the electrode body may also be a laminated electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately laminated via a separator.
[0017] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes: a wound electrode body 14, a nonaqueous electrolyte, and a housing can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The housing can 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the housing can 16 is sealed by a sealing body 17. In the following, for the sake of convenience of description, the battery sealing body 17 side is regarded as the upper side, and the bottom side of the housing can 16 is regarded as the lower side.
[0018] The non-aqueous electrolyte includes: a non-aqueous solvent, and an electrolyte salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents include esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may also contain a halogen-substituted body formed by replacing at least a portion of the hydrogen atoms of these solvents with halogen atoms such as fluorine. Examples of electrolyte salts include lithium salts such as LiPF6. It should be noted that the non-aqueous electrolyte is not limited to a liquid electrolyte, but may also be a solid electrolyte.
[0019] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are wound in a spiral shape so as to be alternately stacked along the radial direction of the electrode body 14. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one size larger than the positive electrode 11. That is, the negative electrode 12 is formed longer in the length direction and the width direction (lateral direction) than the positive electrode 11. The two separators 13 are formed to be at least one size larger than the positive electrode 11, and are arranged, for example, in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0020] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0021] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A grooved portion 22 is formed on the outer can 16, with a portion of the side portion protruding inward to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the grooved portion 22 and the open end of the outer can 16 riveted to the sealing body 1.
[0022] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0023] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , and in particular, the positive electrode active material constituting the positive electrode 11 will be described in detail.
[0024] [positive electrode]
[0025] The positive electrode 11 has: a positive electrode core, and a positive electrode composite material layer arranged on the surface of the positive electrode core. The positive electrode core can use a foil of a metal such as aluminum or aluminum alloy that is stable within the potential range of the positive electrode 11, a thin film of the metal arranged on the surface, etc. The positive electrode composite material layer contains a positive electrode active material, a conductive material, and a binding material, and is preferably arranged on both sides of the positive electrode core. The positive electrode 11 can be made, for example, as follows: a positive electrode composite material slurry containing a positive electrode active material, a conductive material, and a binding material is applied to the positive electrode core, the coating is dried and then compressed, and a positive electrode composite material layer is formed on both sides of the positive electrode core, thereby making it.
[0026] Examples of the conductive material contained in the positive electrode composite material layer include carbon materials such as carbon black, acetylene black, Ketjen black, and graphite. Examples of the binder material contained in the positive electrode composite material layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resin, acrylic resin, polyolefin resin, etc. These resins can also be used in combination with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salts, and polyethylene oxide (PEO), etc.
[0027] The positive electrode active material contains a composition formula Li x Mn y Ni z Al a M b O 2-c F c (wherein, M is two or more elements selected from Ti, Co, Si, Sr, Nb, W, Mo, P, Ca, Mg, Sb, Na, B, V, Cr, Fe, Cu, Zn, Ge, Zr, Ru, K, Bi, 1.0 < x ≤ 1.2, 0.4 ≤ y ≤ 0.8, 0 ≤ z ≤ 0.4, 0 < a < 0.01, 0 < b < 0.03, 0 < c < 0.1, x + y + z + a + b ≤ 2) lithium transition metal composite oxide. This composite oxide is a Li-excess system material with a molar ratio of Li to transition metal exceeding 1, and a specified amount of fluoride ions is introduced, and a part of O is replaced by F.
[0028] The positive electrode active material takes the composite oxide represented by the above composition formula as the main component. Here, the main component refers to the component with the highest mass ratio among the constituent components of the composite oxide. In the positive electrode 11, as the positive electrode active material, a composite oxide other than the composite oxide represented by the above composition formula (for example, a composite oxide that is not a Li-excess system or a composite compound that does not contain fluoride ions) can also be used in combination. The content of the above composite oxide is preferably 50% by mass or more, and can be substantially 100% by mass. It should be noted that the composition of the composite oxide can be measured using an ICP emission spectroscopic analyzer (iCAP6300 manufactured by ThermoFisher Scientific).
[0029] The lithium transition metal composite oxide represented by the above composition formula may contain Ni in addition to Li, Mn, and Al. Two or more elements selected from Ti, Co, Si, Sr, Nb, W, Mo, P, Ca, Mg, Sb, Na, B, V, Cr, Fe, Cu, Zn, Ge, Zr, Ru, K, Bi are also contained as essential components. Among them, Ti, Co, Nb, Ge, Mg, Si, Sr are preferred.
[0030] In the above compositional formula, M is particularly preferably selected from two or more of Ti, Co, and Nb. That is, M is any one of (1) Co and Ti, (2) Co and Nb, (3) Ti and Nb, and (4) Co, Ti, and Nb. In addition, the molar ratio (b) of M is preferably 0 < b < 0.02, more preferably 0.001 ≤ b ≤ 0.015, and particularly preferably 0.0002 ≤ b ≤ 0.010. When the element M is a combination selected from the above (1) to (4), the improvement effect of capacity is more significantly demonstrated.
[0031] In the above compositional formula, the molar ratio (x) of Li is 1.0 < x ≤ 1.2, preferably 1.1 ≤ x ≤ 1.2. The molar ratio (y) of Mn is 0.4 ≤ y ≤ 0.8, preferably 0.45 ≤ y ≤ 0.6. The molar ratio (a) of Al is 0 < a < 0.01, preferably 0.001 ≤ a ≤ 0.007, and more preferably 0.002 ≤ a ≤ 0.005. If the molar ratios of Li, Mn, and Al are within this range, the improvement effect of capacity is more significantly demonstrated. Ni is an optional component, but for example, it is preferably contained in an amount of 0.05 ≤ z ≤ 0.3.
[0032] In the lithium transition metal composite oxide represented by the above compositional formula, the total molar amount (x + y + z + a + b) of Li, Mn, Ni, Al, and M is 2 or less, preferably 2. That is, the composite oxide is preferably a Li-excess type composite oxide and not a cation-excess type composite oxide. In addition, the molar ratio (c) of F is 0 < c ≤ 0.1, preferably 0.05 ≤ x ≤ 0.085. By adding a specified amount of F, the dissolution of the transition metal is suppressed and the durability is improved.
[0033] A specific example of an ideal lithium transition metal composite oxide is a Li-excess type F-containing composite oxide containing Mn, Ni, Al, Co, and at least one of Ti and Nb. This composite oxide substantially does not contain elements other than, for example, Mn, Ni, Al, Co, Ti, Nb, Li, O, and F. The molar ratio of each of Co, Ti, and Nb is preferably 0.01 or less, more preferably 0.001 to 0.007, and particularly preferably 0.002 to 0.005, for example, less than or equal to the molar ratio of Al.
[0034] The lithium transition metal composite oxide of the present embodiment can be synthesized, for example, by mixing a carbonate containing Mn and Ni, a compound containing Al, Co, Ti, Nb, etc. (such as aluminum hydroxide, cobalt sulfate, titanium oxide, niobium oxide, etc.), and lithium fluoride (LiF), and roasting the mixture. An example of the roasting conditions is 700 to 900 °C × 10 to 30 hours.
[0035] [Negative electrode]
[0036] The negative electrode 12 has: a negative electrode core, and a negative electrode composite material layer disposed on the surface of the negative electrode core. The negative electrode core can be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode composite material layer contains a negative electrode active material and a binding material, and is preferably disposed on both sides of the negative electrode core. The negative electrode 12 can be manufactured, for example, by coating a negative electrode composite material slurry containing a negative electrode active material, a conductive material, and a binding material on the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite material layer on both sides of the negative electrode core.
[0037] The negative electrode composite material layer includes, for example, a carbon-based active material that reversibly absorbs and releases lithium ions as a negative electrode active material. Ideal carbon-based active materials are natural graphites such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite (MAG), and artificial graphites such as graphitized mesophase carbon microbeads (MCMB). In addition, in the negative electrode active material, a Si-based active material composed of at least one of Si and a Si-containing compound can be used, and a carbon-based active material and a Si-based active material can also be used in combination.
[0038] As the conductive material contained in the negative electrode composite material layer, carbon materials such as carbon black, acetylene black, Ketjen black, and graphite can be used, as in the case of the positive electrode 11. Among the binding materials contained in the negative electrode composite material layer, fluororesins, PAN, polyimide, acrylic resins, polyolefins, etc. can also be used, as in the case of the positive electrode 11, but styrene-butadiene rubber (SBR) is preferably used. In addition, the negative electrode composite material layer preferably also includes CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, it is ideal to use SBR in combination with CMC or its salt, PAA or its salt.
[0039] [Separator]
[0040] The separator 13 uses a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, non-woven fabrics, etc. can be cited. As the material of the separator 13, polyolefins such as polyethylene, polypropylene, copolymers of ethylene and α-olefins, cellulose, etc. are ideal. The separator 13 can be a single-layer structure or a laminated structure. A heat-resistant layer containing inorganic particles, a heat-resistant layer composed of a heat-resistant resin such as an aromatic polyamide resin, polyimide, polyamide-imide, etc. can be formed on the surface of the separator 13.
[0041] <Example>
[0042] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.
[0043] <Example 1>
[0044] [Synthesis of lithium transition metal composite oxides]
[0045] A carbonate containing Mn and Ni in a molar ratio of 2:1 is mixed with aluminum hydroxide, cobalt sulfate, titanium oxide, and lithium fluoride, and the mixture is calcined at 800°C under an oxygen flow for 20 hours to obtain a composition formula Li 1.167 Mn 0.55 Ni 0.275 Al 0.00 2Co 0.002 Ti 0.002 O 1.92 F 0.08 The lithium transition metal composite oxide shown.
[0046] [Production of positive electrode]
[0047] The above-mentioned lithium transition metal composite oxide is used as the positive electrode active material. The positive electrode active material is mixed with acetylene black and polyvinylidene fluoride at a solid content mass ratio of 7:2:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode composite material slurry. Next, the positive electrode composite material slurry is applied to the positive electrode core formed by aluminum foil, the coating film is dried and compressed, and then cut into a specified electrode size to obtain a positive electrode.
[0048] [Preparation of non-aqueous electrolyte]
[0049] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) are mixed at a predetermined volume ratio, and LiPF6 is added to the mixed solvent to obtain a non-aqueous electrolyte.
[0050] [Production of test battery cells]
[0051] The positive electrode and the negative electrode formed of lithium metal foil are arranged opposite to each other with a separator interposed therebetween to form an electrode body, and the electrode body is housed in a coin-shaped outer can. After the nonaqueous electrolyte is injected into the outer can, the outer can is sealed to obtain a coin-shaped test battery cell (nonaqueous electrolyte secondary battery).
[0052] The initial capacity of the test battery cells was evaluated by the following method, and the evaluation results are shown in Tables 1 to 3 together with the compositions of the positive electrode active materials.
[0053] [Evaluation of initial capacity]
[0054] The test battery cell was CC charged at a constant current of 0.05 C until the battery voltage reached 5.2 V under normal temperature, then CC discharged at a constant current of 0.05 C until the battery voltage reached 2.5 V for 20 minutes, and the discharge capacity was measured.
[0055] <Examples 2 to 7, Comparative Examples 1 to 3>
[0056] In the synthesis of lithium transition metal composite oxides, the types of raw materials and the mixing ratio of the raw materials were changed in a manner to obtain the compositions shown in Tables 1 to 3 (the contents of Ni and Mn were the same as in Example 1). Otherwise, a test battery cell was prepared in the same manner as in Example 1 to evaluate the initial capacity.
[0057] [Table 1]
[0058]
[0059] [Table 2]
[0060]
[0061] [Table 3]
[0062]
[0063] As shown in Table 1, the test cells of the examples using a lithium-excess F-containing composite oxide containing Mn, Ni, and Al and adding two or more elements selected from the group consisting of Co and Ti, Nb, Ge, Mg, and Si as the positive electrode active material have a higher capacity than the test cells of Comparative Example 1 which does not contain Co, Ti, etc. In particular, the test cells of Examples 1, 2, and 6 using composite oxides containing Co and Ti, Co and Nb, and Co and Ti and Nb have a significantly improved initial capacity.
[0064] As shown in Table 2, it is difficult to increase the capacity simply by adding Ti to the lithium-excess F-containing composite oxide containing Mn, Ni, and Al, but the capacity of the test battery cell is specifically improved by adding Co, Nb, Si, etc. in addition to Ti.
[0065] Similarly, as shown in Table 3, it is difficult to increase the capacity simply by adding Nb to the lithium-excess F-containing composite oxide containing Mn, Ni, and Al, but the capacity of the test battery cell is specifically improved by adding Co, Ti, etc. in addition to Nb.
[0066] As described above, by adding two or more specific elements selected from Co, Ti, Nb, etc. together with Al to a lithium-excess F-containing composite oxide containing at least Mn as a transition metal, the capacity can be significantly improved.
[0067] Description of Reference Numerals
[0068] 10Non-aqueous electrolyte secondary battery
[0069] 11 Positive electrode
[0070] 12 Negative electrode
[0071] 13 Dividers
[0072] 14 Electrode body
[0073] 16 shell tank
[0074] 17 Sealing body
[0075] 18, 19 insulation board
[0076] 20 positive lead
[0077] 21 Negative lead
[0078] 22 groove part
[0079] 23 Internal terminal board
[0080] 24 Lower valve body
[0081] 25 Insulation components
[0082] 26 Upper valve body
[0083] 27 Cover
[0084] 28 gasket
Claims
1. A positive electrode active material for a non-aqueous electrolyte secondary battery, comprising a composition formula Li x Mn y Ni z Al a M b O 2-c F c The lithium transition metal composite oxide shown in the formula, wherein M is two or more elements selected from Ti, Co, Si, Sr, Nb, W, Mo, P, Ca, Mg, Sb, Na, B, V, Cr, Fe, Cu, Zn, Ge, Zr, Ru, K, and Bi, 1.0 <x≤1.2、0.4≤y≤0.8、0≤z≤0.4、0.001≤a≤0.007、0<b<0.03、0<c<0.1、x+y+z+a+b≤2。 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein Composition formulaLi x Mn y Ni z Al a M b O 2-c F c wherein M is two or more selected from Ti, Co, and Nb, and the molar ratio (b) of M is 0 <b<0.02。 3 . A non-aqueous electrolyte secondary battery comprising: a positive electrode comprising the positive electrode active material according to claim 1 ; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and a non-aqueous electrolyte.